KONSEP PERKEBUNAN KELAPA SAWIT BERKELANJUTAN - Herda Sabriyah Dara Kospa (UNIVERSITAS INDO GLOBAL MANDIRI, 2016)
This study aimed to design a concept of sustainable palm oil management that took into account economic, socio-political, and environmental aspects using the Agribusiness Partnership approach. The approach used to establish a concept was using synergic relationships between stakeholders (government, private sector and community) with considering sustainable natural resource management aspects. The result considered that the concept of agribusiness partnership in the management of oil palm plantations can be sustainable if it meets three aspects of sustainable management. From the economic point of view, it can increase community's income. Meanwhile, in terms of social welfare, it can improve through the equitable distribution of palm oil. Environmental issues can be maintained because of the synergic cooperation between government, private and community. Keywords : Sustainable palm oil, Oil Palm Cultivation, Integrated Farming Partnership